PERANCANGAN SISTEM MONITORING AKADEMIK SISWA BERBASIS WEB PADA SMP ISLAM TARBIYYATUL FALAH - Lase, Mareanus; Suhardi, Suhardi; Sundari, Sundari; Sopandi, Robi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
SMP Islam Tarbiyyatul Falah is a private educational institution under the auspices of Pondok Pesantren Tarbiyyatul Falah Al-Afandiyah Foundation. Commitment to print students with character, competence, faith and excellence in achievement encourages this educational institution to be more effective and efficient in building communication relation with parents so that student education success can be achieved. But communication between the school and parents is still limited and less efficient, especially for parents of students who are outside the area / city whose children live boarding school. Therefore, by utilizing the progress of information technology that has developed rapidly, SMP Islam Tarbiyyatul Falah initiative to create a dynamic information system and able to represent the academic value of the students so that parents can easily monitor the achievements of his son's academic. The system to be developed is a WEB-based application that uses the waterfall model, starting with the needs analysis, system design and implementation. The tools needed in designing this application are: PHP as scripting language, Apache as web server and MySQL as database processor. Based on the analysis, it can be concluded that the system produced is able to facilitate the parent's students in viewing the student's value such as task score, daily test score, UTS score, and UAS score. In addition, parents can channel the criticism and suggestions through this application easily and can be done anytime, not necessarily in the meeting of parents or other meetings